Implications of Brazilian beef production for food security:: scientific versus industry discourses (Sustainability in Debate, 2021)
This article examines how actors involved in Brazil’s beef production sector define the sector’s role infood security in the context of re-primarization of the economy. Data drawn from 12 semi-structuredinterviews conducted between 2013 and 2014 with representatives of the sector show a contradictionbetween their framings of food security and those found in the scientific literature: while the latterincreasingly stresses the need to reduce production and consumption of meat in order to strengthenfood security in the long term, respondents present beef production as essential to ensure food securityat the national and global levels. Findings therefore indicate that the sector’s discourse paradoxicallyputs the country’s food security at risk.